Estudantes de Pós-Graduação Stricto Sensu : um novo e vultoso grupo social/profissional a ser conhecido - Ciscon-Evangelista, Mariane Ranzani (2014)
The stricto sensu Post-graduation is considered to be one of the most successful segments in the Brazilian Education. It has attracted the interest of young researchers who see in this type of education program the possibility of complementing their training at a time of professional instability. It is also a way to begin a potential academic career. Postgraduate students spend at least six years in the educational development programs. Thus, disregarding the exceptions, they remain financially dependent on their parents and/or partners. This period of financial and professional instability is longer to postgraduate students than it is to their peers in the same age and it implies - temporarily or permanently – disregarding other individual issues such as the difficulty of keeping more stable romantic relationships and of planning to have children. The current study aims to present postgraduate students as a social group that shares social representations. It was done by investigating the way they deal with gender issues during the construction of their academic careers and with their choices concerning romantic relations. The study also aims to investigate these students’ relation with motherhood and fatherhood at the time to build their own family. The five herein conducted studies used different data collection instruments; their major concern points were: postgraduate students, their relationships, their projects for professional future and their family-building plans. These studies showed that postgraduate students are mostly young people. They remain under financial dependence and professional instability when they are still students. Such situation takes them away from stable romantic relationships and becomes a concerning factor regarding parenthood for those who do not have children. It also causes a sense of guilt in students who need to divide their time between the Programs’ demands and their children. The study also enabled identifying traditional social representations of gender, maternity and paternity; although the academic discourse and the popular knowledge are mixed and masked by egalitarian attitudes. The impossibility or greater difficulty to exercise parenting and at the same time attend the Post-graduation course is an anxiety factor for some people. On the other hand, for others, it reinforces the decision to find other forms of satisfaction. In addition, postgraduate students face the demands set by the Post-graduation Programs themselves, since they require long dedication periods without immediate financial return. Therefore, postgraduate students are considered to be professionals because of the demand, but they are not seen as professionals due to lack of immediate return. It is worth conducting further studies focused on post-graduate students as a social and professional group, as well as on Post-graduation professionalization in order to ensure fair labor rights to those who are workers, though (still) students.